Kerja Sama UNHCR dan IOM dalam Menangani Pencari Suaka dan Pengungsi Etnis Rohingya di Indonesia - Arfa Wulandari Tambunan; Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2019)
The conflict that occurred in Myanmar impacts a huge refugee wave in the neighboring countries, one of them in indonesia. Rohingya Ethnic who became minority in the country fled from Myanmar because they have been victims of violence in Myanmar. Rohingya Ethnic who entered the Indonesia’s territory became the focus of UNHCR and IOM in Indonesia. Because, Indonesia has not ratified the 1951 Refugee Convention. This research aims to determine the cooperation of UNHCR and IOM in handling Rohingya Ethnic who entered the Indonesia territory and to describe the impact of  the cooperation. To analyze the cooperation, this research use international cooperation concept with qualitative method and descriptive research by using literature review in data collection. The results show that the cooperation between UNHCR and IOM is carried out with different roles in accordance with mandate which owned by each party and there have also been condition changing of Rohingya from the cooperation.